2005
DOI: 10.1152/jn.00986.2004
|View full text |Cite
|
Sign up to set email alerts
|

Roles of M2 and M4 Muscarinic Receptors in Regulating Acetylcholine Release From Myenteric Neurons of Mouse Ileum

Abstract: We investigated the subtype of presynaptic muscarinic receptors associated with inhibition of acetylcholine (ACh) release in the mouse small intestine. We measured endogenous ACh released from longitudinal muscle with myenteric plexus (LMMP) preparations obtained from M1-M5 receptor knockout (KO) mice. Electrical field stimulation (EFS) increased ACh release in all LMMP preparations obtained from M1-M5 receptor single KO mice. The amounts of ACh released in all preparations were equal to that in the wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 34 publications
2
42
1
3
Order By: Relevance
“…9A). As shown in our previous report, a strong immunoreactivity to an anti-M 2 receptor antibody was observed in the smooth muscle in both circular and longitudinal layers and the myenteric plexus (31). Double staining with anti-M 2 receptor and anti-SP antibodies produced a yellow signal in the myenteric plexus (Fig.…”
Section: G155supporting
confidence: 79%
See 3 more Smart Citations
“…9A). As shown in our previous report, a strong immunoreactivity to an anti-M 2 receptor antibody was observed in the smooth muscle in both circular and longitudinal layers and the myenteric plexus (31). Double staining with anti-M 2 receptor and anti-SP antibodies produced a yellow signal in the myenteric plexus (Fig.…”
Section: G155supporting
confidence: 79%
“…When we examined the coexpression of M 2 receptors and SP in the mouse ileum, an involvement of the M 2 receptor in SP release was revealed. Previously, the specificity of anti-M 2 -receptor antibody has been confirmed in the mouse ileum because the immunoreactivity of this antibody was not observed in M 2 -receptor KO mice (31). In the present study, localization of M 2 receptors on the SP-containing neurons was observed in the myenteric plexus of the mouse ileum.…”
Section: Involvement Of M Receptor In Efs-induced Sustained Contractionsupporting
confidence: 56%
See 2 more Smart Citations
“…It is unlikely that the smaller size of cholinergic EJP in different KO preparations is caused by decreases in the amount of ACh released from the enteric nerves because the amount of released ACh in response to electrical stimulation does not significantly differ among M 2 -KO, M 3 -KO, and wild-type ileal preparations (28). Thus, the data indicate that the wild-type cholinergic EJP is not a simple mixture of M 2 and M 3 responses but may rather arise through a synergy between M 2 and M 3 receptors.…”
Section: Discussionmentioning
confidence: 97%